188 American Spinal Injury Association (ASIA) Impairment Scale (AIS) Conversion Underestimates Neurological Recovery Following Traumatic Spinal Cord Injury. (April 2023) - Choy, Winward; Kyritsis, Nikolaos; Fernandez, Xuan Duong; Ferguson, Adam; Hemmerle, Debra P.; Pascual, Lisa U.; Singh, Vineeta; Talbott, Jason; Pan, Jonathan; Torres, Abel; Whetstone, William; Huie, J. Russell; et al.
Abstract : INTRODUCTION: The predominant tool used in the evaluation of neurological outcomes following spinal cord injury (SCI) is the American Spinal Injury Association (ASIA) Impairment Scale (AIS), calculated within the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). However, there are significant clinical and functional differences within AIS grades A-E that can be better captured by ISNCSCI 0-100 full motor scores. METHODS: 55 patients with acute traumatic SCI who underwent surgery were retrospectively analyzed as part of a prospective cohort study, Transforming Research and Clinical Knowledge in SCI (TRACK-SCI). Clinical, radiographical and treatment parameters were collected, including AIS grades and full motor scores on presentation and discharge, Brain and Spinal Injury Center (BASIC) scores. Multivariable analysis was utilized to evaluate predictors of neurological recovery utilizing AIS grade and motor scores as endpoints. RESULTS: Improvement of at least 1 AIS grade from presentation was noted in 27% of patients (mean improvement of 0.3 AIS grades, p < 0.001) upon discharge. Improvement of total motor scores was noted in 67% with a mean recovery of 8.4 points. The discordance between rate of AIS grade conversion and motor score recovery was greatest in patients with initial AIS grade D (16% vs 72%, respectively). Total motor score improvement was greatest for patients with initial AIS grade C, with a mean improvement of 20 points. Utilizing multivariate analysis, BASIC score and initial total motor score were significant predictors of motor score recovery. However, no variables were prognostic when utilizing AIS conversion as the endpoint. CONCLUSIONS: AIS conversion underestimates true degree of functional improvement following SCI. Changes in full motor score is a more robust outcome metric in the evaluation of factors prognostic of neurological recovery following injury.